Self-Regulated Bilateral Anchoring Enables Efficient Charge Transport Pathways for High-Performance Rigid and Flexible Perovskite Solar Cells - Zheng, Haiying; Liu, Guozhen; Dong, Xinhe; Chen, Feifan; Wang, Chao; Yu, Hongbo; Zhang, Zhihua; Pan, Xu (Nano-Micro Letters, 2025)
Interface modification has been demonstrated as an effective means to enhance the performance of perovskite solar cells. However, the effect depends on the anchoring mode and strength of the interfacial molecules, which determines whether long-term robust interface for carrier viaduct can be achieved under operational light illumination. Herein, we select squaric acid (SA) as the interfacial molecule between the perovskite and SnO2 layer and propose a self-regulated bilateral anchoring strategy. The unique four-membered ring conjugated structure and dicarboxylic acid groups facilitate stable hydrogen bonds and coordination bonds at both SnO2/SA and SA/PbI2 interfaces. The self-transforming property of SA enables the dynamic bilateral anchoring at the buried interface, ultimately releasing residual stress and constructing a stable interfacial molecular bridge. The results show that SA molecular bridge not only can effectively inhibit the generation of diverse charged defects but also serves as an effective electron transport pathway, resulting in improved power conversion efficiency (PCE) from 23.19 to 25.50% and excellent stability at the maximum power point. Additionally, the PCEs of the flexible and large-area (1 cm2) devices were increased to 24.92% and 24.01%, respectively, demonstrating the universal applicability of the bilateral anchoring to PSCs based on different substrates and larger area. Highlights: 1 Robust interface molecular bridge was constructed by employing self-transforming squaric acid (SA) to reduce residual stress and passivate defects at the buried interface. 2 Attributing to the efficient charge transport pathways, the SA-modified perovskite solar cells demonstrate high photovoltaic performance with power conversion efficiency up to 25.50% (rigid) and 24.92% (flexible). 3 The SA-modified devices demonstrate excellent stability under various environmental stress conditions, including humidity, thermal aging, light irradiation, and bending.